Quality of selected anti-retroviral medicines: Tanzania Mainland market as a case study - Sophia Mziray; Betty A. Maganda; Kissa Mwamwitwa; Adam M. Fimbo; Seth Kisenge; Gerald Sambu; Yonah H. Mwalwisi; Adonis Bitegeko; Emmanuel Alphonce; Akida Khea; Danstan H. Shewiyo; Eliangiringa Kaale (BMC, 2021)
Abstract Background Antiretroviral drugs (ARVs) have significantly reduced morbidity, mortality and improved the quality of life of people living with HIV infection. Poor quality ARVs may result in harmful consequences such as adverse drug reactions, treatment failure and development of drug resistant strains and sometimes death, which in turn may undermine the healthcare delivery system. To ensure optimal treatment outcomes, medicines quality control must be undertaken regularly. This study was aimed at evaluating the quality of ARVs circulating on the Tanzania Mainland market. Methods This was a survey study. ARVs samples were collected in 20 regions of Tanzania Mainland, between 2012 and 2018. All sampled ARVs were subjected to screening testing using the Global Pharma Health Fund® Mini-Lab kits. Sampled ARV's that failed screening test or yielded doubtful results and 10 % (10 %) of all that complied with the screening test requirements were selected for full quality control testing. Quality control testing was conducted at the Tanzania Medicines and Medical Devices Authority (TMDA) laboratory a World Health Organisation prequalified. Samples collected from the medicine distribution outlets were also, subjected to product information review. Results A total of 2,630 samples were collected, of which 83.7 % (2200/2630) were from port of entry (POEs). All sampled ARVs were screened and conformed to the specifications, except of the fixed dose combination (FDC) lopinavir/ritonavir 0.27 % (7/2630) and lamivudine/zidovudine/nevirapine 0.27 % (7/2630) that failed the disintegration test. Out of the 100 samples selected for full quality control testing, 3 % of them failed to comply with the specifications, of which FDC stavudine/lamivudine/nevirapine failed disintegration and assay tests 2 % (2/100) and 1 % (1/100), respectively. Samples failing the assay test had low content of stavudine (86.6 %) versus specification limits (90 -110 %). Out of the 430 samples which were subjected to product information review, 25.6 % (110/430) failed to comply with the TMDA packaging and labelling requirements. Conclusions The quality of majority of ARVs circulating on the Tanzania Mainland market was good, even so, significant deficiencies on labelling and packaging were observed. These results call for continuous monitoring of quality of medicines circulating on the Tanzania Mainland market.